Preparation method of a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material

Defectively rich molybdate-based iron tetraoxide nanoparticles were prepared by microemulsion hydrothermal method and plasma treatment, and doped carbon-coated composite materials were formed through carbonization treatment, which solved the problems of low specific capacitance and poor cycle stability performance of existing materials, and achieved high specific capacitance and excellent cycle stability performance.

CN117756186BActive Publication Date: 2025-04-04QIQIHAR UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311795379.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-04-04
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

The specific capacitance of existing molybdate and ferrous tetraoxide materials is low, the cyclic stability performance is poor, and it is easy to cause disordered accumulation and side reactions after nanoification, resulting in poor electrochemical stability.

Method used

Molybdate-based iron tetraoxide nanoparticles were prepared by microemulsion hydrothermal method, and defect-rich composite materials were formed by plasma treatment, and then carbonized under nitrogen protection to form a doped carbon-coated iron tetraoxide flower-like composite material with controllable morphology.

Benefits of technology

It significantly improves the specific capacitance and cyclic stability of the material, optimizes the electrochemical performance, reduces contact with the electrolyte, inhibits adverse chemical reactions, and improves the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117756186B_ABST
    Figure CN117756186B_ABST
Patent Text Reader

Abstract

A method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material. The present invention relates to a method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material. The present invention is to solve the problems of low specific capacitance and poor cycle stability of existing materials. Methods: 1. Molybdate is prepared by microemulsion hydrothermal method; 2. A defect-rich molybdate-based ferroferric oxide flower-shaped composite material is prepared; 3. A defect-rich carbon-coated molybdate-based ferroferric oxide flower-shaped composite material is prepared. The present invention is used for supercapacitor electrode materials, lithium ion batteries and zinc ion battery electrode materials; the assembled supercapacitor has excellent energy density and power density, and has potential application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a morphology-controllable doped carbon-coated molybdate-based ferrosoferric oxide flower-shaped composite material. Background Art

[0002] As a highly efficient electrochemical energy storage device, supercapacitors have been widely used in the fields of automobiles, medical treatment, smart homes, etc. Among the many electrode materials of supercapacitors, molybdates and ferroferric oxide in transition metal oxides have attracted much attention, because both have many advantages such as good theoretical specific capacitance and redox activity, but both have low conductivity, nano-materials increase the surface energy of materials, and make nano-materials very easy to pile up and agglomerate in disorder, and are also prone to side reactions with electrolytes, causing structural degradation and poor electrochemical stability. Summary of the invention

[0003] The invention aims to solve the problems of low specific capacitance and poor cycle stability of existing materials, and provides a method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material.

[0004] The preparation method of a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material of the present invention is carried out according to the following steps:

[0005] 1. Preparation of molybdate by microemulsion hydrothermal method: ① n-octane, n-butanol, hexadecyltrimethylammonium bromide, gadolinium nitrate solution, metal chloride and deionized water are configured into an aqueous solution, and magnetically stirred for 20 to 60 minutes to obtain a homogeneous microemulsion; ② Na2MoO4 and deionized water are configured into an aqueous solution, and magnetically stirred for 20 to 60 minutes to obtain a molybdate microemulsion; ③ The homogeneous microemulsion and the molybdate microemulsion are uniformly mixed under stirring, magnetically stirred for 15 to 30 minutes, and then ultrasonically reacted for 10 to 25 minutes; after the reaction is completed, the mixture is transferred to a hydrothermal reactor, and the hydrothermal reaction is carried out at a temperature of 90 to 150° C. for 18 to 24 hours, and the reactor is naturally cooled to room temperature, the material is taken out, and it is rinsed with ethanol and deionized water for 3 to 5 times in sequence and then dried, and the dried material is heat-treated to obtain molybdate; the metal chloride is Nickel chloride, potassium chloride, ferric chloride, cobalt chloride, zinc chloride or manganese chloride; the concentration of the gadolinium nitrate solution is 0.5-0.6 mol / L; the volume ratio of n-octane to deionized water in step ① is 2.5:(20-40), the volume ratio of n-butanol to deionized water is 1.85:(20-40), the volume ratio of hexadecyltrimethylammonium bromide to deionized water is 1.5 g:(20-40) mL, the volume ratio of gadolinium nitrate solution to deionized water is 5:(20-40), the molar ratio of the metal chloride to the volume ratio of deionized water is (0.4-3.5) mmol:(20-40) mL; the mass fraction of Na2MoO4 in the molybdate microemulsion in step ② is 2.5-9.6%; the volume ratio of the homogeneous microemulsion to the molybdate microemulsion in step ③ is (0.8-1.2):1;

[0006] 2. After mixing molybdate, ferric acetylacetonate and triethylene glycol, stir them magnetically for 10 to 15 minutes, transfer them to a three-necked flask, pass N2 protection and start heating, raise the temperature to 210 to 230°C and keep it warm for 10 to 30 minutes, then quickly raise the temperature to the boiling point of triethylene glycol, boil and reflux at this temperature for 35 to 45 minutes, stop heating, and naturally cool to room temperature to obtain a Fe3O4 nanoparticle reaction solution; centrifuge, wash the Fe3O4 nanoparticle reaction solution with ethyl acetate for 3 to 5 times, place the washed product in a vacuum drying oven at 50 to 75°C and dry it for 22 to 26 hours to obtain a molybdate-based ferric oxide nanoparticle powder; treat the molybdate-based ferric oxide nanoparticle powder with plasma for 1 to 5 minutes to obtain a defect-rich molybdate-based ferric oxide flower-shaped composite material; the mass ratio of the molybdate to the volume of triethylene glycol is 1g:(5 to 6)mL, and the mass ratio of the ferric acetylacetonate to the volume of triethylene glycol is 1g:(6 to 7)mL;

[0007] 3. Disperse the defect-rich molybdate-based ferroferric oxide flower-shaped composite material and glucose in deionized water, stir magnetically to disperse them uniformly, and then transfer them to a stainless steel autoclave lined with polytetrafluoroethylene, keep heating at a temperature of 150-200°C for 8-14 hours, finally cool the mixture to room temperature, wash it with distilled water for 3-5 times, and obtain a powder after drying. The powder is carbonized at 740-780°C for 3-6 hours under nitrogen protection to obtain a defect-rich carbon-coated molybdate-based ferroferric oxide flower-shaped composite material; the mass ratio of the defect-rich molybdate-based ferroferric oxide flower-shaped composite material to glucose is (3.24-5.87):(8.4-12.56), and the mass ratio of the defect-rich molybdate-based ferroferric oxide flower-shaped composite material to deionized water is (3.24-5.87) g:200 mL.

[0008] Advantages of the present invention:

[0009] The whole process of the present invention is safe, pollution-free, and the operation flow is relatively simple; the obtained composite material has abundant oxygen vacancies, and reasonable defects lead to greatly improved electrochemical performance; the obtained composite material has excellent specific capacitance and cycle stability; the prepared electrode material is widely used and can be applied to supercapacitor electrode materials, lithium ion batteries and zinc ion battery electrode materials; the assembled supercapacitor has excellent energy density and power density, and has potential application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a morphology analysis diagram of the doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material of Example 1; wherein a represents a scanning electron microscope and b represents a transmission electron microscope;

[0011] Figure 2 This is an XPS analysis chart of O in the doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material of Example 1;

[0012] Figure 3 This is a graph showing the electrochemical performance of the doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material of Example 1; wherein a represents the specific capacitance at different current densities, and b represents the cycle stability performance test;

[0013] Figure 4 For AMoO 4-x @Fe3O4@C(A=K, Zn, Fe, Co, Ni, Mn) / / Energy density and power density diagram during CNTs; where a represents energy density and b represents power density. DETAILED DESCRIPTION

[0014] Specific implementation method 1: In this implementation method, a method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material is carried out according to the following steps:

[0015] 1. Preparation of molybdate by microemulsion hydrothermal method: ① n-octane, n-butanol, hexadecyltrimethylammonium bromide, gadolinium nitrate solution, metal chloride and deionized water are configured into an aqueous solution, and magnetically stirred for 20 to 60 minutes to obtain a homogeneous microemulsion; ② Na2MoO4 and deionized water are configured into an aqueous solution, and magnetically stirred for 20 to 60 minutes to obtain a molybdate microemulsion; ③ The homogeneous microemulsion and the molybdate microemulsion are uniformly mixed under stirring, magnetically stirred for 15 to 30 minutes, and then ultrasonically reacted for 10 to 25 minutes; after the reaction is completed, the mixture is transferred to a hydrothermal reactor, and the hydrothermal reaction is carried out at a temperature of 90 to 150° C. for 18 to 24 hours, and the reactor is naturally cooled to room temperature, the material is taken out, and it is rinsed with ethanol and deionized water for 3 to 5 times in sequence and then dried, and the dried material is heat-treated to obtain molybdate; the metal chloride is Nickel chloride, potassium chloride, ferric chloride, cobalt chloride, zinc chloride or manganese chloride; the concentration of the gadolinium nitrate solution is 0.5-0.6 mol / L; the volume ratio of n-octane to deionized water in step ① is 2.5:(20-40), the volume ratio of n-butanol to deionized water is 1.85:(20-40), the volume ratio of hexadecyltrimethylammonium bromide to deionized water is 1.5 g:(20-40) mL, the volume ratio of gadolinium nitrate solution to deionized water is 5:(20-40), the molar ratio of the metal chloride to the volume ratio of deionized water is (0.4-3.5) mmol:(20-40) mL; the mass fraction of Na2MoO4 in the molybdate microemulsion in step ② is 2.5-9.6%; the volume ratio of the homogeneous microemulsion to the molybdate microemulsion in step ③ is (0.8-1.2):1;

[0016] 2. After mixing molybdate, ferric acetylacetonate and triethylene glycol, stir them magnetically for 10 to 15 minutes, transfer them to a three-necked flask, pass N2 protection and start heating, raise the temperature to 210 to 230°C and keep it warm for 10 to 30 minutes, then quickly raise the temperature to the boiling point of triethylene glycol, boil and reflux at this temperature for 35 to 45 minutes, stop heating, and naturally cool to room temperature to obtain a Fe3O4 nanoparticle reaction solution; centrifuge, wash the Fe3O4 nanoparticle reaction solution with ethyl acetate for 3 to 5 times, place the washed product in a vacuum drying oven at 50 to 75°C and dry it for 22 to 26 hours to obtain a molybdate-based ferric oxide nanoparticle powder; treat the molybdate-based ferric oxide nanoparticle powder with plasma for 1 to 5 minutes to obtain a defect-rich molybdate-based ferric oxide flower-shaped composite material; the mass ratio of the molybdate to the volume of triethylene glycol is 1g:(5 to 6)mL, and the mass ratio of the ferric acetylacetonate to the volume of triethylene glycol is 1g:(6 to 7)mL;

[0017] 3. Disperse the defect-rich molybdate-based ferroferric oxide flower-like composite material and glucose in deionized water, stir them evenly with magnetic stirring, transfer them to a stainless steel autoclave with a polytetrafluoroethylene lining, keep heating at a temperature of 150-200°C for 8-14 hours, finally cool the mixture to room temperature, wash it with distilled water 3-5 times, and obtain powder after drying. Carbonize the powder at 740-780°C for 3-6 hours under nitrogen protection to obtain a defect-rich carbon-coated molybdate-based ferroferric oxide flower-like composite material; the mass ratio of the defect-rich molybdate-based ferroferric oxide flower-like composite material to glucose is (3.24-5.87):(8.4-12.56), and the mass ratio of the defect-rich molybdate-based ferroferric oxide flower-like composite material to deionized water is (3.24-5.87) g:200 mL. Improve the contact interface conductivity, enhance the collection of carriers, and effectively optimize the electrochemical properties of the material, especially the improvement of specific capacity. In addition, we deposit carbon materials on the surface of the active material, and the surface coating structure forms a protective film, which effectively prevents the internal contact of the material with the electrolyte, thereby inhibiting adverse chemical reactions at the positive electrode / electrolyte interface, reducing the dissolution of transition metal ions and the precipitation of oxygen, and optimizing the material's cycle stability performance.

[0018] The present invention selects molybdate and ferroferric oxide, electrode materials with relatively excellent theoretical specific capacitance, as the main substances. By regulating the ratio of each metal ion in molybdate and utilizing the synergistic effect of ferroferric oxide, the contact interface conductivity is improved, the collection of carriers is enhanced, the electrochemical performance of the material is effectively optimized, and the specific capacitance of the two is significantly improved. In addition, by doping rare earth elements and plasma technology treatment, defects are effectively formed in the product, which stimulates the resonance effect between ions. The improvement of the conductive performance is achieved by regulating the concentration of semiconductor carriers, thereby optimizing the electrochemical performance of the product. Finally, we deposit carbon material on the surface of the active material, and the surface coating structure forms a protective film, which effectively prevents the contact between the material and the electrolyte, thereby inhibiting the unfavorable chemical reaction at the positive electrode / electrolyte interface, reducing the dissolution of transition metal ions and the precipitation of oxygen, and optimizing the cyclic stability of the material.

[0019] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: in step 1③, the hydrothermal reaction is carried out at a temperature of 120° C. for 24 hours. The rest is the same as specific embodiment 1.

[0020] Specific implementation method 3: This implementation method is different from specific implementation method 1 in that the ultrasonic reaction in step 1 ③ adopts an interval ultrasonic method of ultrasonic 5s and rest 5s, and the ultrasonic power is 600W. Other aspects are the same as specific implementation method 1.

[0021] Specific embodiment 4: This embodiment differs from specific embodiment 1 in that the drying in step 1③ is carried out in a constant temperature drying oven at 60°C for 12 hours. The rest is the same as specific embodiment 1.

[0022] Specific embodiment 5: This embodiment differs from specific embodiment 1 in that the heat treatment in step 1③ is carried out in a muffle furnace at a temperature of 350° C. for 1.5 h. The rest is the same as specific embodiment 1.

[0023] Specific embodiment six: This embodiment is different from the specific embodiment one in that: when the metal chloride in step 1① is nickel chloride, the molar ratio of nickel chloride to the volume ratio of deionized water is (0.4-2) mmol: (20-40) mL; when the metal chloride is potassium chloride, the molar ratio of potassium chloride to the volume ratio of deionized water is (0.5-1.5) mmol: (20-40) mL; when the metal chloride is ferric chloride, the molar ratio of ferric chloride to the volume ratio of deionized water is (1-2.5) mmol: (20-40) mL; )mmol:(20~40)mL; when the metal chloride is cobalt chloride, the molar ratio of cobalt chloride to the volume ratio of deionized water is (1~3.5)mmol:(20~40)mL; when the metal chloride is zinc chloride, the molar ratio of zinc chloride to the volume ratio of deionized water is (0.5~1.5)mmol:(20~40)mL; when the metal chloride is manganese chloride, the molar ratio of manganese chloride to the volume ratio of deionized water is (0.5~3)mmol:(20~40)mL. The rest is the same as the specific embodiment 1.

[0024] Specific implementation method 7: This implementation method is different from the specific implementation method 1 in that: in step 2, the temperature is raised to 220° C. and kept for 20 minutes. The rest is the same as the specific implementation method 1.

[0025] Specific embodiment eight: This embodiment differs from specific embodiment one in that the mass ratio of molybdate to triethylene glycol in step two is 3.24 g:18 mL, and the mass ratio of ferric acetylacetonate to triethylene glycol is 2.85 g:18 mL. Others are the same as specific embodiment one.

[0026] Specific embodiment 9: This embodiment differs from specific embodiment 1 in that: in step 3, the heating is maintained at 180° C. for 10 hours. The rest is the same as specific embodiment 1.

[0027] Specific embodiment 10: This embodiment differs from specific embodiment 1 in that: in step 3, the powder is carbonized at 750° C. for 5 h under nitrogen protection. The rest is the same as specific embodiment 1.

[0028] The beneficial effects of the present invention are verified by the following examples:

[0029] Example 1: A method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material is carried out according to the following steps:

[0030] 1. Preparation of molybdate by microemulsion hydrothermal method: ① Prepare an aqueous solution of 2.5 mL of n-octane, 1.85 mL of n-butanol, 1.5 g of hexadecyltrimethylammonium bromide, 5 mL of 0.5 mol / L gadolinium nitrate solution, 2.3 g of nickel chloride and 20-40 mL of deionized water, and stir magnetically for 20-60 min to obtain a homogeneous microemulsion; ② Prepare an aqueous solution of 4.8 g of Na2MoO4 and 20 mL of deionized water, and stir magnetically for 20-60 min to obtain a molybdate microemulsion; ③ Prepare 8.4 mL of homogeneous microemulsion and 6.2 mL of molybdate The root microemulsion is mixed evenly under stirring, magnetically stirred for 15 to 30 minutes, and then ultrasonically treated for 5 seconds and rested for 5 seconds, with an ultrasonic power of 600W and an ultrasonic reaction for 10 to 25 minutes; after the reaction is completed, it is transferred to a hydrothermal kettle, and the hydrothermal reaction is carried out at a temperature of 120°C for 24 hours. The reactor is naturally cooled to room temperature, the material is taken out, and it is rinsed with ethanol and deionized water for 3 to 5 times in turn, and then treated in a constant temperature drying oven at a temperature of 60°C for 12 hours. The dried material is treated in a muffle furnace at a temperature of 350°C for 1.5 hours to obtain molybdate;

[0031] 2. Mix 3.24 g of molybdate, 2.85 g of ferric acetylacetonate and 18 mL of triethylene glycol, stir magnetically for 10 to 15 min, transfer to a three-necked flask, pass N2 protection and start heating, raise the temperature to 220°C and keep warm for 20 min, then quickly raise the temperature to the boiling point of triethylene glycol, boil and reflux at this temperature for 35 to 45 min, stop heating, and naturally cool to room temperature to obtain a Fe3O4 nanoparticle reaction solution; centrifuge, wash the Fe3O4 nanoparticle reaction solution with ethyl acetate for 3 to 5 times, dry the washed product in a vacuum drying oven at 50 to 75°C for 22 to 26 h to obtain a molybdate-based ferrosoferric oxide nanoparticle powder; treat the molybdate-based ferrosoferric oxide nanoparticle powder with plasma for 1 to 5 min to obtain a defect-rich molybdate-based ferrosoferric oxide flower-like composite material;

[0032] 3. Disperse 3.24-5.87 g of defect-rich molybdate-based ferroferric oxide flower-like composite material and 8.4-12.56 g of glucose in 200 mL of deionized water, stir magnetically to disperse evenly, transfer to a stainless steel autoclave with a polytetrafluoroethylene lining, and heat at 180°C for 10 h. Finally, cool the mixture to room temperature, wash it with distilled water 3-5 times, and dry it to obtain a powder. Carbonize the powder at 750°C under nitrogen protection for 5 h to obtain a defect-rich carbon-coated molybdate-based ferroferric oxide flower-like composite material.

[0033] Example 2: This example differs from Example 1 in that: Step 1 ① 2.5 mL of n-octane, 1.85 mL of n-butanol, 1.5 g of hexadecyltrimethylammonium bromide, 5 mL of 0.5 mol / L gadolinium nitrate, 2.8 g of potassium chloride and 20-40 mL of deionized water are prepared into an aqueous solution, and magnetically stirred for 20-60 min to obtain a homogeneous microemulsion. The rest is the same as Example 1.

[0034] Example 3: This example differs from Example 1 in that: Step 1 ① 2.5 mL of n-octane, 1.85 mL of n-butanol, 1.5 g of hexadecyltrimethylammonium bromide, 5 mL of 0.5 mol / L gadolinium nitrate, 1.6 g of ferric chloride and 20-40 mL of deionized water are prepared into an aqueous solution, and magnetically stirred for 20-60 min to obtain a homogeneous microemulsion. The rest is the same as Example 1.

[0035] Example 4: This example differs from Example 1 in that: Step 1 ① 2.5 mL of n-octane, 1.85 mL of n-butanol, 1.5 g of hexadecyltrimethylammonium bromide, 5 mL of 0.5 mol / L gadolinium nitrate, 2.2 g of cobalt chloride and 20-40 mL of deionized water are prepared into an aqueous solution, and magnetically stirred for 20-60 min to obtain a homogeneous microemulsion. The rest is the same as Example 1.

[0036] Example 5: This example differs from Example 1 in that: Step 1 ① 2.5 mL of n-octane, 1.85 mL of n-butanol, 1.5 g of hexadecyltrimethylammonium bromide, 5 mL of 0.5 mol / L gadolinium nitrate, 3.2 g of zinc chloride and 20-40 mL of deionized water are prepared into an aqueous solution, and magnetically stirred for 20-60 min to obtain a homogeneous microemulsion. The rest is the same as Example 1.

[0037] Example 6: This example is different from Example 1 in that: Step 1 ① 2.5 mL of n-octane, 1.85 mL of n-butanol, 1.5 g of hexadecyltrimethylammonium bromide, 5 mL of 0.5 mol / L gadolinium nitrate, 2.5 g of manganese chloride and 20-40 mL of deionized water are prepared into an aqueous solution, and magnetically stirred for 20-60 min to obtain a homogeneous microemulsion. The rest is the same as Example 1.

[0038] Figure 1 For the morphology characterization of Example 1, Figure 1 (a) It can be seen that the product has a flower-like structure, and the size of the flower is about 2um. Figure 1 (b) is the TEM test of the product. There is a light-colored area on the surface of the product, which indicates that it is covered with a layer of carbon material. In addition, the color of the middle area of ​​the product is obviously inconsistent with that of the outside, indicating that the product is composed of two parts, molybdate-based ferroferric oxide as the core part and the carbon material coated on the outside as the shell part.

[0039] Figure 2 This is the XPS analysis of O in Example 1, which shows a prominent peak at 530.0 eV, which is a characteristic of metal oxygen bond, and a defect oxygen peak at 532.4 eV. This shows that the product prepared by this method has oxygen defects, and the content of oxygen defects is 8.3%.

[0040] Figure 3 For specific capacity and cycle stability performance test. Figure 3 It can be seen that the prepared composite material has good electrochemical properties. At a current density of 1A / g, the specific capacity is as high as 2385F / g. At a current density of 3A / g, the specific capacity is as high as 2168F / g. At a current density of 5A / g, the specific capacity is as high as 1967F / g. At a current density of 10A / g, the specific capacity is as high as 1705F / g. At a high current density of 15A / g, the specific capacity is still as high as 1622F / g. Even at a high current density of 20A / g, the specific capacity is still as high as 1516F / g. Figure 3 b is the cycle stability performance test of the composite material at a current density of 5A / g. The results show that after 10,000 cycles, the specific capacity is as high as 1959F / g, the capacity retention rate reaches 99.6%, and the cycle stability performance is good.

[0041] Assembly of asymmetric capacitor device: Use doped carbon-coated molybdate-based ferroferric oxide as the positive electrode, carbon nanotubes as the negative electrode, 3M KOH aqueous solution as the electrolyte, and place the diaphragm between the positive and negative electrodes to assemble an asymmetric supercapacitor device.

[0042] Figure 4 The specific capacity of the asymmetric supercapacitor prepared by using carbon-coated molybdate-based ferroferric oxide as the positive electrode and carbon nanotubes as the negative electrode. Figure 4 It can be found that the device has good specific capacitance. At a current density of 1A / g, the specific capacitance is as high as 320F / g. At a current density of 3A / g, the specific capacitance is as high as 302F / g. At a current density of 5A / g, the specific capacitance is as high as 286F / g. At a current density of 10A / g, the specific capacitance is as high as 275F / g. At a high current density of 15A / g, the specific capacitance is still as high as 261F / g. Even at a high current density of 20A / g, the specific capacitance is still as high as 239F / g. Figure 4 b is the cycle stability performance test and coulomb efficiency test diagram of the device. It can be found that after the device is cycled 3000 times, the cycle stability performance reaches 99.2% and the coulomb efficiency is close to 80%, indicating that the device has good cycle stability performance.

Claims

1. A method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material, characterized in that The preparation method of the morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material is carried out according to the following steps:

1. Preparation of molybdate by microemulsion hydrothermal method: ① n-octane, n-butanol, hexadecyltrimethylammonium bromide, gadolinium nitrate solution, metal chloride and deionized water are configured into an aqueous solution, and magnetically stirred for 20 to 60 minutes to obtain a homogeneous microemulsion; ② Na2MoO4 and deionized water are configured into an aqueous solution, and magnetically stirred for 20 to 60 minutes to obtain a molybdate microemulsion; ③ The homogeneous microemulsion and the molybdate microemulsion are uniformly mixed under stirring, magnetically stirred for 15 to 30 minutes, and then ultrasonically reacted for 10 to 25 minutes; after the reaction is completed, the mixture is transferred to a hydrothermal reactor, and the hydrothermal reaction is carried out at a temperature of 90 to 150° C. for 18 to 24 hours, and the reactor is naturally cooled to room temperature, the material is taken out, and it is rinsed with ethanol and deionized water for 3 to 5 times in sequence and then dried, and the dried material is heat-treated to obtain molybdate; the metal chloride is Nickel chloride, potassium chloride, ferric chloride, cobalt chloride, zinc chloride or manganese chloride; the concentration of the gadolinium nitrate solution is 0.5-0.6 mol / L; the volume ratio of n-octane to deionized water in step ① is 2.5:(20-40), the volume ratio of n-butanol to deionized water is 1.85:(20-40), the volume ratio of hexadecyltrimethylammonium bromide to deionized water is 1.5 g:(20-40) mL, the volume ratio of gadolinium nitrate solution to deionized water is 5:(20-40), the molar ratio of the metal chloride to the volume ratio of deionized water is (0.4-3.5) mmol:(20-40) mL; the mass fraction of Na2MoO4 in the molybdate microemulsion in step ② is 2.5-9.6%; the volume ratio of the homogeneous microemulsion to the molybdate microemulsion in step ③ is (0.8-1.2):1; 2. After mixing molybdate, ferric acetylacetonate and triethylene glycol, stir them magnetically for 10 to 15 minutes, transfer them to a three-necked flask, pass N2 protection and start heating, raise the temperature to 210 to 230°C and keep it warm for 10 to 30 minutes, then quickly raise the temperature to the boiling point of triethylene glycol, boil and reflux at this temperature for 35 to 45 minutes, stop heating, and naturally cool to room temperature to obtain a Fe3O4 nanoparticle reaction solution; centrifuge, wash the Fe3O4 nanoparticle reaction solution with ethyl acetate for 3 to 5 times, place the washed product in a vacuum drying oven at 50 to 75°C and dry it for 22 to 26 hours to obtain a molybdate-based ferric oxide nanoparticle powder; treat the molybdate-based ferric oxide nanoparticle powder with plasma for 1 to 5 minutes to obtain a defect-rich molybdate-based ferric oxide flower-shaped composite material; the mass ratio of the molybdate to the volume of triethylene glycol is 1g:(5 to 6)mL, and the mass ratio of the ferric acetylacetonate to the volume of triethylene glycol is 1g:(6 to 7)mL; 3. Disperse the defect-rich molybdate-based ferroferric oxide flower-shaped composite material and glucose in deionized water, stir magnetically to disperse them uniformly, and then transfer them to a stainless steel autoclave lined with polytetrafluoroethylene, keep heating at a temperature of 150-200°C for 8-14 hours, finally cool the mixture to room temperature, wash it with distilled water for 3-5 times, and obtain a powder after drying. The powder is carbonized at 740-780°C for 3-6 hours under nitrogen protection to obtain a defect-rich carbon-coated molybdate-based ferroferric oxide flower-shaped composite material; the mass ratio of the defect-rich molybdate-based ferroferric oxide flower-shaped composite material to glucose is (3.24-5.87):(8.4-12.56), and the mass ratio of the defect-rich molybdate-based ferroferric oxide flower-shaped composite material to deionized water is (3.24-5.87) g:200 mL.

2. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that In step 1③, the hydrothermal reaction is carried out at a temperature of 120°C for 24 hours.

3. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that The ultrasonic reaction in step 1③ adopts an interval ultrasonic method of ultrasonic 5s and rest 5s, and the ultrasonic power is 600W.

4. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that The drying in step 1③ is carried out in a constant temperature drying oven at 60°C for 12 hours.

5. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that The heat treatment in step 1③ is carried out in a muffle furnace at a temperature of 350°C for 1.5 hours.

6. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that When the metal chloride in step 1① is nickel chloride, the molar ratio of nickel chloride to the volume ratio of deionized water is (0.4-2) mmol: (20-40) mL; when the metal chloride is potassium chloride, the molar ratio of potassium chloride to the volume ratio of deionized water is (0.5-1.5) mmol: (20-40) mL; when the metal chloride is ferric chloride, the molar ratio of ferric chloride to the volume ratio of deionized water is (1-2.5) mmol: (20-40) mL; when the metal chloride is cobalt chloride, the molar ratio of cobalt chloride to the volume ratio of deionized water is (1-3.5) mmol: (20-40) mL; when the metal chloride is zinc chloride, the molar ratio of zinc chloride to the volume ratio of deionized water is (0.5-1.5) mmol: (20-40) mL; when the metal chloride is manganese chloride, the molar ratio of manganese chloride to the volume ratio of deionized water is (0.5-3) mmol: (20-40) mL.

7. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that In step 2, the temperature was raised to 220°C and kept for 20 min.

8. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that In step 2, the mass ratio of molybdate to triethylene glycol is 3.24 g:18 mL, and the mass ratio of ferric acetylacetonate to triethylene glycol is 2.85 g:18 mL.

9. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that In step 3, the heating is maintained at 180° C. for 10 h.

10. The method for preparing a morphology-controllable doped carbon-coated molybdate-based ferroferric oxide flower-shaped composite material according to claim 1, characterized in that In step 3, the powder is carbonized at 750° C. for 5 h under nitrogen protection.

Citation Information

Patent Citations

  • Preparation method of controllable-shape NaGd(MoO4)2:Eu<3+> luminescent powder

    CN106544019A

  • Ecological restoration agent containing amidoxime and selective enrichment technology thereof on uranyl

    CN108325505A